Evaluasi Kebijakan Terhadap Kewenangan Pemerintah Provinsi Kepulauan Riau Dalam Pemungutan Retribusi Labuh Jangkar - Sapitri, Intan; Safitri, Tasya Hirdia; Supratman, Heru (Bahasa Indonesia, 2024)
Maritime resource management is a crucial aspect in the economic development of a region, espically in the Riau Island region which has implemented policies to increase the utilization of maritime resources through anchoring. Anchoring is a condition of anchoring using an anchor at sea for a specific purpose. Ship anchoring activities that utilize the waters of the Riau Island and there is no system for collecting ship anchor fees. This research aims to evaluate these policies and analyze authority. Riau Island Provincial Government in implementing the levy collection.